Contributed Reports of Widely Felt Earthquakes in California, United States: If They Felt it, Did They Report it? - Hough, Susan E. (Frontiers in Earth Science, 2021)
In a recent study, Hough and Martin (2021) considered the extent to which socioeconomic factors influence the numbers and distribution of contributed reports available to characterize the effects of both historical and recent large earthquakes. In this study I explore the question further, focusing on analysis of widely felt earthquakes near major population centers in northern and southern California since 2002. For earthquakes through 2014, there is a correlation between average household income in a postal ZIP code and the rate of responses to the DYFI system. The correlation appears to be less pronounced since 2018. I show, however, that for five earthquakes between 2011 and 2021 that generated especially uniform shaking across the greater Los Angeles, California, region, response rate varies by two orders of magnitude across the region, with a clear correlation with demographics, and consistent spatial patterns in response rate for earthquakes 10 years apart. While there is no evidence that uneven DYFI participation in California impacts significantly the reliability of intensity data collected, the results reveal that DYFI participation is significantly higher in affluent parts of southern California compared to economically disadvantaged areas.